Motivation Matters: Understanding Job Satisfaction Drivers Among Generation Z Employess in the Banking Sector - Noviyanti, Indah Salsa; Rimadias, Santi (The Eastasouth Management and Business, 2025)
This study investigates the influence of career commitment, employee training, and workload on job satisfaction, with motivation as a mediating variable, among permanent Generation Z employees at Bank X in the DKI Jakarta region. Utilizing a quantitative approach and Partial Least Squares Structural Equation Modeling (PLS-SEM), data were collected from 100 respondents and analyzed using SmartPLS 4.0. The results reveal that career commitment, employee training, and workload do not have a direct and significant effect on job satisfaction. However, employee motivation significantly influences job satisfaction and serves as a mediating variable between career commitment and workload on job satisfaction. Interestingly, employee training does not show a significant indirect effect through motivation. These findings emphasize the critical role of motivation in enhancing job satisfaction among Generation Z employees. Managerial implications highlight the need to redesign training programs, develop career paths that align with Gen Z expectations, and establish workload management strategies that foster a motivating work environment.